AUTOMATED BLOOD PRESSURE MEASUREMENT IN PATIENTS WITH HYPERTENSION AND ATRIAL FIBRILLATION. DATA FROM THE ESH RESEARCH PROJECT "MANAGEMENT OF ARTERIAL HYPERTENSION IN PATIENTS WITH HIGH BLOOD PRESSURE AND ATRIAL FIBRILLATION". (June 2018) - Salvetti, M.; Jelakovic, B.; Dorobantu, M.; Viigimaa, M.; Manolis, A.J.; Redon, J.; Parati, G.; Rosei, E. Agabiti
Abstract : Objective: Atrial fibrillation (AF) is a frequent complication of long lasting hypertension, and carries a high risk of morbidity and mortality as well as of cardiovascular events. AF is also responsible for possible errors in blood pressure (BP) measurement. Limited information is available on the accuracy of blood pressure measurements when automated oscillometric (OSC) devices are used instead of the standard auscultatory approach (AUSC). The aim of this analysis was to compare blood pressure values measured using either a mercury sphygmomanometer or an automated electronic device in patients with AF. The analysis was limited to 353 patients (mean CHA2DSVA2SC score 3.9), enrolled in the international multicenter ESH Research Project on arterial hypertension and atrial fibrillation, in whom BP was measured 4 times with the standard AUSC approach (according to Guidelines) and 4 times with an OSC device. Results mean age was 72 ± 11 (range 20–94), BMI 28 ± 5, mean CHA2S2VASC 3.9. Mean BP values were 130.3 ± 19.5 for AUSC-SBP and 131.5 ± 20.1 for OSC-SBP and 75.8 ± 11.4 for AUSC-DBP and 76.5 ± 12.3 for OSC-DBP. Correlation coefficients between automated and manual blood pressure measurements were: r = 0.917 for SBP and r = 0.856 for DBP (p < 0.0001). The difference between the oscillometric and manual measurement was on average of 1.2 mmHg for systolic BP (SBP) and of 0.7 mmHg for diastolic BP (DBP). The standard deviations (SD) of the differences were, respectively, 8.07 and 6.39, and progressively increased wen 4, 3, 2 or 1 measurements were used. At Bland-Altman analysis the limits of agreement were −17 to 14.7 mmHg for SBP and -13.3 to 11.8 for DBP. Conclusions: In patients with hypertension and AF measurement of BP values with oscillometric devices provides similar BP values, with SD at the upper limit of AAMI criterion for the validation of devices, at least when 4 BP measurements are performed.